Development of E-LKPD Using the Wizer.me Website Based on Discovery Learning in Science and Technology Learning in Class IV Elementary Schools - Lara Syafira; Yeni Erita (JURNAL PENDIDIKAN IPS, 2025)
The development of E-LKPD based on the Wizer.me platform with the Discovery Learning model is the aim of this research. It is designed for use in science learning in fourth grade elementary schools. This research is motivated by the fact that LKPD are still in printed form, these LKPD are usually plain, less interesting, and do not encourage students to participate actively in the learning process. In addition, the use of technology in providing learning materials that suit modern educational needs is still limited. For this research, the ADDIE model is used as a Research and Development (R&D) approach, which consists of five stages: Analysis, Design, Development, Implementation, and Evaluation. Validation by material, language and media experts gave a score of 93.54% so that the product was included in the "Very Valid" category. The practicality test at SD IT Ridhotullah gave practicality scores for teachers and students of 94.54% and 95.52% respectively; at SDN 15 Ulu Gadut, the ratings were 98.18% and 93.91% respectively; and at SD Dian Andalas, the ratings were 96.36% and 94.65% respectively. The results of the N-Gain analysis effectiveness test showed 80.94% at SD IT Ridhotullah, 82.40% at SDN 15 Ulu Gadut, and 86.15% at SD Dian Andalas. The E-LKPD developed through Wizer.me and based on the Discovery Learning approach has proven to be valid, practical and effective for improving science and science learning in fourth grade elementary school.